(3GdhSW GdeOQSj s (3HjFI QjGOjI ddJYde hGdJYdje HMSH GdfXGe GdJYdjej GdLOjOs - (3GdOcJhQ jhSa Ndjd eGQhf s ((3dHfGfs (3GdeDSSI GdMOjKI ddcJGH s, 2015)
(3GdcJGH bSeGf(B: (3bSe Ghd NUU ddhSW GdeOQSj h OhQg GdJQHhj hGdbSe GdKGfj jOhQ Mhd GdechfGJ GdHTQjI ef eSDhd heYdes